2017
DOI: 10.1080/02791072.2017.1370748
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of High-Risk and Low-Risk Alcohol Use among College Students in Kerala, India

Abstract: This study describes the prevalence and correlates of alcohol use among college students in Ernakulam, Kerala State, India. A total of 5784 students from 58 colleges selected by stratified random sampling completed a questionnaire incorporating standardized instruments. The prevalence of lifetime alcohol use was 21.4% with a male predominance. Among users, low-risk, hazardous, and dependent use were 80.2%, 18.3% and 0.9% respectively. Initiation was mostly with friends (45.3%). Both low-risk and high-risk alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…17 Though it has been consistently reported that alcohol use impairs academic performance irrespective of gender, 1,2 in our sample, only the male students using alcohol had impaired academic performance. A significantly higher proportion of males in our study, as reported in the prior paper, reported hazardous use (males-27.8%; females-5.4%), 5 suggesting that only hazardous use may correlate with academic decline.…”
Section: Discussionsupporting
confidence: 60%
“…17 Though it has been consistently reported that alcohol use impairs academic performance irrespective of gender, 1,2 in our sample, only the male students using alcohol had impaired academic performance. A significantly higher proportion of males in our study, as reported in the prior paper, reported hazardous use (males-27.8%; females-5.4%), 5 suggesting that only hazardous use may correlate with academic decline.…”
Section: Discussionsupporting
confidence: 60%
“…Two unique factors may have contributed to this higher rate. First, there was approximately 3-4 fold higher personal use of alcohol in males when compared to females [20]. The link between respondent-alcohol use and increased 'risk of harm from others drinking' have been consistently reported [3,4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists various studies indicating an interdependence between the risk of alcohol use and ADHD patients [4,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Several studies have reported that ADHD and alcohol abuse have a direct positive correlation [30][31][32][33][34][35][36][37][38][39][40][41]. Nevertheless, there have been many contradictory reports showing that the risk of alcohol abuse does not depend on ADHD [4,[42][43][44].…”
Section: Reviewmentioning
confidence: 99%
“…Many studies have shown that a connection between childhood ADHD and alcohol abuse is common (see Table 1). Jaisooya et al, 2017, conducted a study on 5784 students and concluded that those students who reported high risk for alcohol use showed ADHD symptoms [40]. People who self-reported with ADHD showed a higher likelihood of alcohol abuse [41].…”
Section: Adhd Leads To Alcohol Abusementioning
confidence: 99%